2007
DOI: 10.1103/physrevlett.99.140405
|View full text |Cite
|
Sign up to set email alerts
|

Infinite-Randomness Fixed Points for Chains of Non-Abelian Quasiparticles

Abstract: One dimensional chains of non-Abelian quasiparticles described by SU (2) k Chern-Simons-Witten theory can enter random singlet phases analogous to that of a random chain of ordinary spin-1/2 particles (corresponding to k → ∞). For k = 2 this phase provides a random singlet description of the infinite randomness fixed point of the critical transverse field Ising model. The entanglement entropy of a region of size L in these phases scales as SL ≃ ln d 3 log 2 L for large L, where d is the quantum dimension of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 25 publications
2
104
0
3
Order By: Relevance
“…This goal was partially achieved in Ref. 21 for a golden chain which contains only AFM bonds. As we shall see, including FM bonds in this analysis reveals a new fixed point, where the number of FM and AFM bonds is the same.…”
Section: B Flow Equations For the Fibonacci Chainmentioning
confidence: 99%
See 3 more Smart Citations
“…This goal was partially achieved in Ref. 21 for a golden chain which contains only AFM bonds. As we shall see, including FM bonds in this analysis reveals a new fixed point, where the number of FM and AFM bonds is the same.…”
Section: B Flow Equations For the Fibonacci Chainmentioning
confidence: 99%
“…Carrying this out, Ref. 21 showed that for large number N of singlets, the entropy is asymptotically N log 2 . Thus the asymptotic contribution of each singlet is log 2 .…”
Section: ͑13͒mentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] Because of the unique structure of their Hilbert spaces, disordered anyonic chains are particularly amenable to treatment via strong randomness renormalization-group ͑RG͒ methods and indeed have been shown to exhibit infiniterandomness fixed points. 11,12 They are thus an especially fertile ground for trying to discover and classify new universality classes of strongly random behavior. Indeed, even though no new universality classes were found, Ref.…”
Section: Introductionmentioning
confidence: 99%